Fabrication and electrical characterizations of SGOI tunnel FETs with gate length down to 50 nm. (January 2016) - Le Royer, C.; Villalon, A.; Hutin, L.; Martinie, S.; Nguyen, P.; Barraud, S.; Glowacki, F.; Allain, F.; Bernier, N.; Cristoloveanu, S.; Vinet, M.
Abstract: We report the fabrication and the characterization of tunnel FETs fabricated on SiGe-On-Insulator with a High-κ Metal Gate (HKMG) CMOS process. The beneficial impact of low band gap SiGe channel on I D ( V G ) characteristics is presented and analyzed: compressive Si0.75 Ge0.25 enables to increase by a factor of 25 the saturation currents, even at small gate length ( L G  = 50 nm). This large gain is due to the threshold voltage shift and to enhanced intrinsic band-to-band tunneling injection (both related to the narrow band gap of SiGe channels).